2001
DOI: 10.1093/bja/86.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from propofol anaesthesia supplemented with remifentanil

Abstract: We have examined the effects on recovery end-points of supplementation of a propofol-based anaesthetic with remifentanil. After induction of anaesthesia with propofol and remifentanil 1.0 microg kg(-1), 15 patients each were randomly allocated to target plasma propofol concentrations of 2, 3, 4 or 5 microg ml(-1) for maintenance of anaesthesia. Remifentanil was administered by infusion for supplementation in doses required for maintenance of adequate anaesthesia. All patients received 50% nitrous oxide in oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
(7 reference statements)
0
27
0
3
Order By: Relevance
“…This is the first study to assess the effect of adding remifentanil to propofol on recovery parameters in spontaneous ventilation anesthesia. O'Hare et al 15 demonstrated shorter recovery times when maintenance of anesthesia is changed from using a higher dose of propofol with a lower dose of remifentanil to a regimen with a lower dose of propofol and a higher dose of remifentanil. However, in that study ventilation was controlled, so these data are not comparable with the data presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to assess the effect of adding remifentanil to propofol on recovery parameters in spontaneous ventilation anesthesia. O'Hare et al 15 demonstrated shorter recovery times when maintenance of anesthesia is changed from using a higher dose of propofol with a lower dose of remifentanil to a regimen with a lower dose of propofol and a higher dose of remifentanil. However, in that study ventilation was controlled, so these data are not comparable with the data presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…In our endoscopy center, propofol is also administered by an anesthesiologist or nurse anesthetist. Propofol provides equal or better control and more rapid recovery when compared with midazolam for sedation (O'Hare et al, 2001). Initial intravenous bolus dose of propofol is 1.0 mg/kg and is followed by 0.5 mg/kg, and the repeated dose is needed.…”
Section: Sedative Drugs 321 Propofolmentioning
confidence: 99%
“…Remifentanil has been shown to have propofolsaving effect, thus allowing a lower dose of propofol to be used for the maintenance of anesthesia [20] . A combination of remifentanil and propofol is considered safe, effective and acceptable for sedation in children under going gastrointestinal endoscopy [21] .…”
Section: Remifentanilmentioning
confidence: 99%
“…The authors recommend this combination for sedation in children in a hospital setting in presence of an anesthesiologist. When compared with midazolam for sedation, propofol provides equal or better control and more rapid recovery [20] .…”
Section: Propofolmentioning
confidence: 99%